A Genotype First Approach in Currarino Syndrome - Milani, Donatella; Bonarrigo, Francesca Andrea; Guerneri, Silvana; Baccarin, Marco; Menni, Francesca; Esposito, Susanna (International Journal of Pediatrics and Child Health, 2013)
We describe a 3-year-old girl presenting with psychomotor delay and facial dysmorphisms. Array CGH showed a region of duplication and a contiguous deletion on the long arm of chromosome 7. The genetic results allowed us to discover previously unsuspected sacral agenesis and presacral teratoma typical of Currarino syndrome, whose gene maps to the deleted region. So we used a genotype first approach to better discover the phenotypic traits of our patient, highlighting the advantages of an appropriate clinical use of genetic methods.